Assessing physical activity, mental health, and quality of life among older adults in Tehran, Iran: A cross-sectional study - Mohammad VaezMousavi; Hadi Nobari; Amir Shams; Hamed Abbasi; Parvaneh Shamsipour-Dehkordi; Fariba Mohamadi; Andrew J. Brinkley; Mahdi Bayati; Lara Carneiro (PLoS ONE, 2025)
Background The World Health Organisation (WHO/EMRO) funded research aimed to evaluate the effects of physical activity (PA) levels and their relationship with mental health and quality of life (QoL) among older adults in Tehran, Iran. Methods A cross-sectional design was used, and data from five different regions were collected from 7500 individuals aged over 60 years using four questionnaires: The International PA Questionnaire (IPAQ), Quality of Life Questionnaire (WHOQOL-26), General Health Questionnaire (GHQ-28), and a preliminary individual characteristics questionnaire. The IPAQ assessed PA, while the GHQ-28 evaluated mental health. The WHOQOL-26 assessed quality of life in four areas: physical health, psychological well-being, social relationships, and environment. Data analysis was conducted on MLwiN 3.05, whereby multilevel regression models were constructed. Results Results indicated that most participants had low levels of PA, with 74.4% meeting low levels of PA. No meaningful variation in mental health or QoL was attributable to PA behavior across regions. However, age, marital status, dependents, and MET PA were found to significantly predict mental health scores, while MET PA, age, number of dependents, social welfare, gender, and education significantly predicted QoL values. Conclusion The study highlights the need for executive support, coordination mechanisms, and appropriate infrastructures to improve the level of PA among Iranian older adults and promote mental well-being in this population.